2020
DOI: 10.3390/agronomy10010119
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of the Nutrient Uptake Requirements of Peanut

Abstract: Understanding the characteristics of the balanced nutrient requirements for peanut to achieve target yields is paramount when formulating fertilizer management strategies to increase yields and avoid fertilizer loss. Nutritional requirement estimation models can provide effective alternatives for the estimation of the optimum crop balanced nutrient requirements under varied agricultural conditions which are less time consuming and expensive. In the present study, the quantitative estimation of the optimum crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…The average pod K concentration was similar to that reported (7.1 g kg −1 ) by Xie et al (2020), whereas the straw K concentration was greater than 12.9 g kg −1 of their reports. The requirement of N (47.7 kg), P (7.1 kg), and K (20.7 kg) per Mg pod yield in this study were greater relative to that reported (38.4 kg N, 4.3 kg P, and 14.0 kg K) by Xie et al (2020). Most of the data in this study is derived from optimum fertilization treatments, with an average pod yield of 4.48 Mg ha −1 .…”
Section: Crop Sciencesupporting
confidence: 87%
See 1 more Smart Citation
“…The average pod K concentration was similar to that reported (7.1 g kg −1 ) by Xie et al (2020), whereas the straw K concentration was greater than 12.9 g kg −1 of their reports. The requirement of N (47.7 kg), P (7.1 kg), and K (20.7 kg) per Mg pod yield in this study were greater relative to that reported (38.4 kg N, 4.3 kg P, and 14.0 kg K) by Xie et al (2020). Most of the data in this study is derived from optimum fertilization treatments, with an average pod yield of 4.48 Mg ha −1 .…”
Section: Crop Sciencesupporting
confidence: 87%
“…Peanut total P uptake also increased with increasing pod yield, with roughly 50% of the variation in P uptake explained by pod yield (Figure 3A). Across all data, peanut P requirement per Mg pod yield averaged 7.1 kg, which was greater than the 4.3 kg reported by Xie et al (2020) but lower than the 7.9 kg documented by Wu et al (2019). Differences in P requirements per Mg pod yield might be due to pooling of dataset from different locations and experiments.…”
Section: Peanut P Uptake and Requirement Across Increasing Pod Yieldcontrasting
confidence: 63%
“…Using the QUEFTS model (Quantitative Evaluation of the Fertility of Tropical Soils), Xie et al [16] demonstrated a linear accumulation of nutrients with increasing yield. Nutrient accumulation decreased slightly after yields reached~60% to 70% of the potential yield.…”
Section: Nutrient Rates-recommendationsmentioning
confidence: 99%
“…These results indicated that nutrition management practices had a great influence on IE values. Additionally, due to the diversities of plant growth characteristics and other factors, the IEs of N, P, and K were greater than other crops such as maize [30], soybean [14], peanut [53], and potato [33].…”
Section: Internal Efficiency and Reciprocal Internal Efficiencymentioning
confidence: 99%